Interplay between a foreshock bubble and a hot flow anomaly forming along the same rotational discontinuity - Turc,L; Archer,MO; Zhou,H; PfauKempf,Y; Suni,J; Kajdi,P; BlancoCano,X; Dahani,S; Battarbee,M; Raptis,S; Liu,TZ; Zhang,H; et al. (Geophysical Research Letters, 2025)
Solar wind directional discontinuities can generate transient mesoscale structures such as foreshock bubbles and hot flow anomalies (HFAs) upstream of Earth's bow shock. These structures can have a global impact on near-Earth space, so understanding their formation conditions is essential. We investigate foreshock transient generation at a rotational discontinuity using a global 2D hybrid-Vlasov simulation. As expected, a foreshock bubble forms on the sunward side of the discontinuity. Later, when the discontinuity reaches the shock, new structures identified as HFAs develop, despite the initial discontinuity not being favorable to HFA formation. We demonstrate that the foreshock bubble provides the necessary conditions for their generation. We then investigate the evolution of the transient structures and the large-scale bow shock deformation they induce. Our results provide new insights on the formation and evolution of foreshock transients and their impact on the shock.